2013
DOI: 10.1155/2013/451956
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Posterior Dynamic Stabilization Systems

Abstract: Spinal rigid instrumentations have been used to fuse and stabilize spinal segments as a surgical treatment for various spinal disorders to date. This technology provides immediate stability after surgery until the natural fusion mass develops. At present, rigid fixation is the current gold standard in surgical treatment of chronic back pain spinal disorders. However, such systems have several drawbacks such as higher mechanical stress on the adjacent segment, leading to long-term degenerative changes and hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…8 Many in vitro and biomechanical studies have shown that this system can restrain the amount of flexibility through polyethylene terephthalate cords and polycarbonate urethane spacers. 9 10 11 Contrary to PLIF, which may lead to a rigid connection of the operative level, this system is designed to stabilize the operated segment while allowing some mobility, therefore, it may preserve a better of lumbar mobility than PLIF. 12 …”
Section: Introductionmentioning
confidence: 99%
“…8 Many in vitro and biomechanical studies have shown that this system can restrain the amount of flexibility through polyethylene terephthalate cords and polycarbonate urethane spacers. 9 10 11 Contrary to PLIF, which may lead to a rigid connection of the operative level, this system is designed to stabilize the operated segment while allowing some mobility, therefore, it may preserve a better of lumbar mobility than PLIF. 12 …”
Section: Introductionmentioning
confidence: 99%
“…1,4,26 The main design goal of such devices is to apply a distraction force to the processes and prevent further extension of the segment. As a result, ISP devices help to relieve the symptoms of neurogenic intermittent claudication associated with spinal stenosis.…”
mentioning
confidence: 99%
“…They are also designed to allow motion during flexion, lateral bending, and axial rotation at the treated segment because they reduce adjacent-level effects. 4,6 Of all ISP devices, the X-Stop device (Saint Francis Medical Technologies Inc.) has been documented most extensively in the literature. 20 It has 2 lateral wings to prevent unnecessary displacements.…”
mentioning
confidence: 99%
“…Posterior dynamic stabilization has become a widely spread surgical intervention that can be performed using various types of implants [5,15]. Most of these implants are, however, mechanically complex and not always biomimetic.…”
Section: Discussionmentioning
confidence: 99%